Ihdad Perspektif Hadis dan Eksistensinya di Era Society 4.0: (Kajian Hadis Tematik) - Khairiyatin , Khairiyatin (El Nubuwwah Jurnal Studi Hadis, 2023)
This research is entitled ihdad perspective on hadith and its existence in the era of society 4.0 (thematic hadith studies). In the hadith of the Prophet there are several hadiths related to ihdad, in which ihdad itself is a word that comes from the Arabic al-hidad which means prohibition or prevention. Some opinions also say that ihdad is not wearing jewelry, leaving fragrances, nail polish, combing hair, using henna and eye shadow. The purpose of this study is to find out the provisions of ihdad according to the Prophet's Hadith and to describe how they exist in the era of society of 4.0. This type of research is descriptive qualitative research. The data collection method is in the form of literature (library research) related to the theme raised. The results of this research show that several hadiths related to ihdad are considered Shahih and also Hasan Shahih, these hadiths have the same theme with different narrators and sanad. Then regarding the existence of ihdad itself, it still exists and is still being carried out as a sign of condolences for the departure of her husband and to prevent slander from arising.